Current Status and Global Research Trend Patterns of Insect Meal in Aquaculture From Scientometric Perspective: (2013–2022) - Raghuvaran N.; Tincy Varghese; Prasanta Jana; Angela Brighty R. J.; Muthiah Sethupathy A.; Sudarshan S.; Yahya Bin Abdullah Alrashdi; Adel Ehab Ibrahim; Sami El Deeb (Aquaculture Nutrition)
In the past decade, insect meal has gained popularity in the animal feed industry, particularly in aquafeed, due to rising costs and decreased availability of fish meal (FM) and fish oil. Initially met with skepticism, insect meal is now seen as a promising ingredient because of its high nutrient profile. Research worldwide is exploring its potential as a FM replacement. Insects are abundant, nutritious, and environmentally friendly, as they can be reared on organic waste, minimizing the need for land, water, and energy. This research aims at obtaining a comprehensive and in-depth understanding of the current status and research trend patterns in this research field. To achieve this goal, this study conducts a mini systematic review and scientometric analysis of the global research published from 2013 to 2022 on the usage of insect meal in aquaculture. In the scientometric analysis, a total of 354 papers published by 1800 authors in 124 different journals from the Web of Science (WoS) core collection were analyzed, evaluating the number of publications, most relevant authors, organizations, top cited countries, most globally cited publications, and trending research themes in this field. The result showed that the University of Turin was the leading organization in insect meal research, whereas aquaculture was the leading journal, and author Laura Gasco was the prominent researcher in this field in the studied time frame (2013–2022). Italy was the leading country in Europe, while China dominated Asia in terms of the number of publications. The annual growth rate in insect meal research was found to be positive (23.11%), with 36.95 average citations per document. This study helps practitioners and scholars understand the current state of insect meal in aquaculture and identifies research requirements that can benefit both academia and industry.